Relação do tempo de trânsito faríngeo e presença de resíduo com dispneia e função pulmonar na doença pulmonar obstrutiva crônica - Prestes, Daniele (2019)
Swallowing is a physiological action involving a great process of voluntary and involuntary actions and its function is to conduct food from the oral cavity to the stomach in a safe way, mainly to protect the airway. In addition, it requires the concise coordination of four essential phases for the transit of the food bolus from the mouth to the stomach, beginning with the oral and oral preparatory phase (voluntary) and later pharyngeal and esophageal phases (involuntary), any change in one or more of these phases is defined as dysphagia. The etiology of swallowing changes in Chronic Obstructive Pulmonary Disease (COPD) has not yet been well established. In this context, assessing the different phases of swallowing along with characteristic changes of COPD becomes important. Thus, the present research had as objective to relate the pharyngeal transit time and the presence of residual in vallecula and pyriform sinuses with dyspnea and pulmonary function in individuals with COPD. This is an observational, descriptive and cross-sectional study with adult individuals, both sexes, with clinical diagnosis performed by the pulmonologist and spirometric of COPD, referred to the Pulmonary Rehabilitation Program by the Department of Pulmonology of the Hospital Universitário de Santa Maria. The sample was submitted to the anthropometric evaluation, to calculate the Body Mass Index (BMI), physical therapy evaluation, to characterize the impact of the disease on the individual, dyspnea and lung function. The speech-language evaluation was performed by videofluoroscopy of swallowing for analysis of the variables oral transit time, pharyngeal transit time and pharyngeal residues. The exams were analyzed using Kinovea® software by three blinded judges. We analyzed 19 individuals (11 males and 8 females), with a mean of 63.8 years and eutrophic. There was no relation regarding TTF variables with pulmonary function and pharyngeal residue with dyspnea. TTF, when compared with normal, was increased. We conclude that individuals with COPD, regardless of the severity of the disease, did not show changes in TTF related deglutition and presence of residuals in valleculae and pyriform sinuses.